Mathematical Models for Determination of Specific Energy Need for Heating and Cooling of the Administrative Building - I. Deshko, V; Yu. Bilous, I (International Journal of Engineering and Technology, 2018)
According to the building energy balance, most of the resources are spent on maintaining a comfortable indoor microclimate. To estimate the energy resources rational use and to determine building energy efficiency, specific indicators are used per unit area and/or volume. In this paper, a comparative analysis of various approaches to determination of energy need for heating and cooling that have been used or are introduced in Ukraine and the peculiarities of different climatic data application is carried out. The differences in application of considered methods are established. The analysis of various averaging time intervals (monthly, daily average and hourly) for climatic parameters change in dynamic models during the heating period application influence on heating and cooling load change is carried out. Specific energy need has been established according to different methods and a comparison with the current normative values in Ukraine has been made.